Efeito protetor da N-acetilcisteína sobre o estresse oxidativo causado pela administração crônica de aspartame em ratos - Finamor, Isabela Andres (2015)
This thesis evaluated the N-acetylcysteine effects (150 mg/kg, intraperitoneal) on the biochemical and oxidative changes caused by the daily oral consumption of aspartame at 40 mg/kg for six weeks by rats. For this purpose, were performed two experiments, in both the animals were divided in four groups: Control – received both aspartame and Nacetylcysteine vehicles; NAC – received aspartame vehicle, and N-acetylcysteine; ASP – received aspartame, and N-acetylcysteine vehicle; ASP-NAC – received both aspartame and N-acetylcysteine. The aspartame was administrated for six weeks; whereas the Nacetylcysteine was injected only in the fifth and sixth week. After it, the animals were anesthetized, their blood was removed, the serum was separated; and then, the rats were euthanized by exsanguination. In the first experiment, the serum was used for the measurement of glucose levels and also biomarkers of kidney and liver damage; the whole brain, liver and kidney were removed for the analysis of the oxidative stress parameters. As the results, in general, aspartame caused hyperglycemia and oxidative stress in the whole brain, and hepatic and renal tissues. N-acetylcysteine treatment protected all these tissues against the oxidative damage (lipid peroxidation and protein carbonylation), in especial, by promoting the reduced glutathione (GSH) synthesis, inducing the enzymes related to its metabolism (glutathione peroxidase (GPx), glutathione reductase (GR) and glutathione Stransferase), and elevating the ascorbic acid levels and total reactive antioxidant potential. In the second experiment, the serum was utilized for the determination of glucose content and lipid profile; the liver was removed for glucose measurement; and the whole brain was separated in the following structures: cerebral cortex, cerebellum, brainstem, and hypothalamus; in which was held the research of the oxidative stress biomarkers. The aspartame consumption caused an elevated glucose production in the liver, hyperglycemia, hypertriglyceridemia, hypercholesterolemia; and oxidative stress in all the brain regions. Although N-acetylcysteine treatment did not reduce neither the synthesis of liver glucose nor the hyperglycemia, it normalized the triglycerides and high-density lipoprotein cholesterol in the serum. This antioxidative treatment also protected all the brain regions against the lipid peroxidation, increased GSH levels and induced its associated enzymes (GPx and GR), triggering different defensive responses according each brain region. Therefore, the data of this thesis suggest that N-acetylcysteine attenuates the oxidative damage generated by the intake of this artificial sweetener. More studies were needed to elucidate the signaling pathways involved in this process; as well as to determine the aspartame metabolites levels (phenylalanine, aspartate and methanol) found in the rat plasma and brain.